Motion imagery processing and exploitation (MIPE) - Cordova, Amado; Millard, Lindsay; Menthe, Lance; Guffey, Robert A.; Rhodes, Carl A., 1970- (RAND, 2013)
This report defines and investigates the potential of motion imagery processing and exploitation (MIPE) systems, which can help U.S. military intelligence analysts optimize their response to the current information deluge and enable them to continue to exploit a wide range of motion imagery collections. The authors define MIPE as the collection of capabilities and enabling technologies, tools, and systems that aid analysts in the detection, identification, and tracking of objects of interest (OOIs), such as humans and vehicles; in the identification of activities of interest (AOIs); and in the characterization of relationships between and among OOIs and AOIs in live and archival video. The authors examined the needs of motion imagery analysts, identified MIPE capabilities that could assist in meeting those needs, and assessed the technical readiness of MIPE systems. Recommendations include using MIPE systems to focus analysts' attention on significant video frames, investing in systems that take advantage of many sources of information, and standardizing MIPE test plans.